Soldiers on international missions : there and back again - Lyk-Jensen, Stéphanie Vincent; Pedersen, Peder J. (Emerald Publishing Limited, 2019)
This book contributes important new insights into how deployment on international military missions affects soldiers and their lives. Using both quantitative data and in-depth interviews, the authors provide a longitudinal perspective covering the participants in these missions before, during, and after deployment on a large range of life outcomes. The research centres around four key themes; who are the men and women who choose to be deployed; why do they choose to be deployed; what challenges do these soldiers face before, during, and after returning home from a mission; and what are the consequences of deployment for the soldiers' individual lives?Danish soldiers provide an illustrative study and data is drawn from administrative registries and is supplemented with broader surveys of present and former soldiers, in-depth interviews of parents and other relatives, and support group professionals.Using specifically constructed datasets and comparing these soldiers with relevant control groups, this book offers a unique analysis of the impact of deployment on important issues such as personal finances, the labour market, criminal activity, smoking and drinking, and overall health. Mapping a full portrait of the men and women who choose to be deployed, and explaining both their initial motivations, this book highlights the challenges they face before and during deployment and upon returning home.